2019
DOI: 10.1021/acs.accounts.9b00144
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Molecular Carbon Nanostructures

Abstract: CONSPECTUS:Chirality is a fascinating property present in naturally occurring and artificial molecules and materials, observable as chiroptical behavior. The emerging area of carbon nanostructures has undergone tremendous development, with a wide variety of carbon nanoforms reported over the last two decades. However, despite interest in merging chirality and nanocarbons, this has been successfully achieved only in empty fullerenes, whereas in other kinds of fullerenes or carbon nanostructures such as carbon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(68 citation statements)
references
References 57 publications
0
62
0
1
Order By: Relevance
“…Besides, metallo‐peptides find applications in the same field with the advantage that peptides can be conveniently prepared via automated methodologies . Moreover, application of different type of nanostructures underwent incredible expansion over the last years including in catalysis . The most developed materials include chiral nanostructures mainly organized in nanotube, nanocage and micelles and based on the assembly of small and medium sized molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, metallo‐peptides find applications in the same field with the advantage that peptides can be conveniently prepared via automated methodologies . Moreover, application of different type of nanostructures underwent incredible expansion over the last years including in catalysis . The most developed materials include chiral nanostructures mainly organized in nanotube, nanocage and micelles and based on the assembly of small and medium sized molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To date, chiral fullerene derivatives have mostly been explored as an academic curiosity and in limited applications, with a notable exception perhaps being enantioselective catalysis. [ 23 ] Given the importance of this material class to organic electronic devices, it is curious that single‐enantiomer fullerene devices are yet to be explored in this context. This may be because the opportunities provided by chiral organic semiconducting materials are, in general, underexploited in technological applications.…”
Section: Figurementioning
confidence: 99%
“…The introduction of chirality to TMOs has revolutionized the motif of TMOs with respect to their applications in area of chiroptical sensing and detection, enantioselective catalysis, biological‐tissue‐based therapy, and chirality‐based devices. Since a body of related reviews has well summarized the details about the possible applications of chiral inorganic NCs, [ 6,47–55 ] we would prefer only to highlight some representative examples of chiral TMOs here: 1)Chiroptical sensing and detection: Xu and co‐workers [ 56 ] reported recently that chiral CuxOS@ZIF‐8 nanostructures can be used as ultrasensitive probe for detection of H 2 S in vivo with the limit of detection of 0.3 × 10 −9 and 2.2 × 10 −9 m for CD and fluorescence methods because H 2 S can reduce the chiroptical intensity and increase the fluorescent signal of the nanostructures ( Figure A). Jiang's group [ 57 ] also demonstrated that cysteine‐capped Au/Fe 3 O 4 NPs can enantioselectively detect the percentage of d ‐tyrosine in a mixture of enantiomers via cysteine as the chiral selector. 2)Enantioselective catalysis: Qu and co‐workers [ 58 ] developed phenylalanine‐modified cerium oxide nanoparticles (CeNPs) as chiral nanozyme for stereoselective oxidation of 3,4‐dihydroxyphenylalanine (DOPA) enantiomers where l ‐CeNP showed higher catalytic ability for oxidation of d ‐DOPA while d ‐CeNP were more effective to l ‐DOPA (Figure 4B).…”
Section: Applications and Perspectivesmentioning
confidence: 99%